NEW DESIGN OPTIONS FOR THE IMPROVEMENT OF THE MUTRIKU POWER PLANT (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The research based on the development of OWC devices continues growing and nowadays there are endless options that have already been studied. From the type of turbine and its control, to the most efficient energy conversion system or design, the OWC technology needs to be further developed in order to be economically attractive. This research studies several possibilities to improve the efficiency of the Mutriku breakwater wave plant. On the one hand, the L-shape configuration of this plant allows studying a new configuration based on the coupling of the well-known U-shape [1], to create a new L+U-shape breakwater. In addition, the installation of harbor-walls has been proven as a promising option to enhance the interior damping of the camera [2], and this option seems to be very promising because of the design of the Mutriku plant allows its performance. Finally, a design based on the sharp-edges round off its being studied in order to reduce the energy losses and therefore enhance the energy harnessing of the plant. The experimental work has been carried out in the 12.5 m long wave flume located at the laboratory of Fluid Mechanics of the Energy Engineering Department (UPV/EHU). The physically constructed OWC device corresponds to one of the cameras installed at the Mutriku breakwater wave plant, an isolated camera, according to the construction plan and applying a 1:36 scale. All the experiments were carried out at two tides that correspond to the medium and maximum equinoctial live tides of Mutriku location. According to the information of the Basque Coast sea states [3], a constant incident regular waves of 30 mm were generated at several periods: 0.7